Effect of Lower Limb Muscle Fatigue on Fall Risk for Transfemoral Amputee: A Pilot Study - Mohd Khairuddin Mohd Safee; Noor Azuan Abu Osman (Occupational Therapy International)
Muscle fatigue is a decline in muscle maximum force during contraction and can influence the fall risk among people. This study is aimed at identifying the effect of fatigue on prospective fall risk in transfemoral amputees (TFA). Fourteen subjects were involved in this study with TFA (34.7±8.1 yrs, n=7) and normal subjects (31.1±7.4 yrs, n=7). Fatigue of lower limb muscles was induced with the fatigue protocol. Subjects were tested prefatigue and postfatigue using the standardized fall risk assessment. All results were calculated and compared between pre- and postfatigue to identify fatigue’s effect on both groups of subjects. The results showed that the fall risk increased significantly during pre- and postfatigue for TFA (p=0.018), while there were no significant differences in normal subjects (p=0.149). Meanwhile, the fall risk between TFA and normal subjects for prefatigue (p=0.082) and postfatigue (p=0.084) also showed no significant differences. The percentage (%) of increased fall risk for TFA was 19.2% compared to normal subjects only 16.7%. However, 61.4% increased of % fall risk in TFA after fatigue by using the baseline of the normal subject as the normalized % of fall risk. The increasing fall risks for TFA after fatigue are three times higher than the potential fall risk in normal subjects. The result indicates that they need to perform more precautions while prolonging lower limb activities. These results showed the implications of fatigue that can increase the fall risk due to muscle fatigue from repetitive and prolonged activities. Therefore, rehabilitation programs can be done very safely and precisely so that therapists can pursue fitness without aggravating existing injuries.